PROTOTYPE OF HOUSE FIRE EARLY DETECTION SYSTEM USING FLAME SENSOR WITH TELEGRAM NOTIFICATION VIA THINGER.IO - Wahjudi, Dody; Sudaryanto, Eko; Ayu Margiyanti, Niken Dwi; Darmawan, Isra' Nuur (Journal of Electronic and Electrical Power Applications, 2024)
This research is based on the problem of gas leakage which is one of the factors causing fires to occur. Too slow a response of the homeowner to the occurrence of a fire disaster is a factor in fires that can cause loss of life and property that is not small. As an effort to prevent things that are not expected, a system that can detect fires effectively is needed. Designing a fire detection system that supports IoT (Internet Of Things) so that it can be monitored remotely is a suitable preventive alternative. Therefore, the design of a fire detection system using the NodeMCU ESP8266 microcontroller and input Flame sensor that can detect the presence of fire with a minimum detection distance of 10cm with an average voltage output of 5.076V while, the maximum detection distance is 100cm with an average voltage output of 5.066V. MQ-2 sensor to detect gas particles with an average output voltage of 4.99V. Dust sensors can detect paper smoke particles with an average voltage output of 5.066V at a smoke density of 848.90 while cigarette smoke with an average voltage output of 5.038 at a smoke density of 849.87. If one of the sensors detects a potential fire, it will automatically send a message to Telegram accompanied by a buzzer and LED that lights up as a warning sign. Thinger.io software to monitor data changes in the system.